Extraction, characterisation and bioassay activities of allelochemicals from 11 allelopathic species - Razanah binti Ramya @ Abd Rahim
This study established that allelopathic species from different plant groups of tree, fern, sedge and herbaceous differ greatly with respect to types and concentrations of allelochemical content. A total of 11 allelopathic species were evaluated for quantitative and qualitative phenolic compounds composition in different plant groups, extraction method, solvents and bioassay activities. The allelopathic effect towards weeds germination and growth were also tested by developing an in vitro model system. The main phenolic compounds identified in 11 allelopathic species were 4-Hydroxybenzoic acid, Caffeic acid, Vanillic acid, trans-p-Coumaric acid, Ferulic acid, 3-Coumaric acid and 2-Coumaric acid. The ratio of these phenolic compounds varies between plant groups. Tree group was found to have the highest total phenolic content followed by a group of ferns, herbaceous and sedges. 4-Hydroxybenzoic acid (3.00 to 1169.53 μg/g DW), Vanillic acid (1.88 to 1594.08 μg/g DW), trans-p-Coumaric acid (1.50 to 1171.28 μg/g DW), Ferulic acid (1.68 to 1876.0 μg/g DW), 3-Coumaric acid (15.58 to 933.63 μg/g DW) and 2-Coumaric acid (230.30 μg/g DW) were detected predominantly in tree group whereas Caffeic acid was found predominantly in herbaceous group (1.95 to 3375.23 μg/g DW). Marked differences were observed between the trees, ferns, herbaceous and sedges. Therefore, 11 allelopathic species were further analysed over bioassay activities to assess antimicrobial and weeds inhibitory. Antimicrobial activities of 11 allelopathic species in this study confirmed that the antifungal assay showed lower inhibitory than antibacterial assay. A. auriculiformis, M. cajuputi, D. linearis and H. malayana showed great antibacterial activity towards S. aureus, S. epidermis, E. coli, MRSA and P. aeruginosa whereas for antifungal only C. albicans and Fusarium sp were inhibited. A high-throughput in vitro model system for investigating allelopathic effect in weeds was developed and validated by assessing the allelopathic effects at a different concentration, a period of time and type of weed. The most influential factor appeared to be allelochemical extract concentration. The higher the concentration, the greater the inhibitory effect regardless type of weed.